“The Clock Is Ticking”: The Timely Management of a Painful Skin Rash in a Seventy-Year-Old Woman - Susan Thomas; Folashade Omole; Vijaykumar G. Patel; Michelle L. Nichols (Case Reports in Medicine)
Necrotizing fasciitis is an uncommon but a potentially fatal condition and can affect any part of the body. Most patients have pre-existing conditions that render them susceptible to infection, although etiology is unclear. Diagnosis is primarily clinical and is often delayed because of the unfamiliarity of the condition among clinicians. Management consists of immediate resuscitation, early surgical debridement, and administration of broad spectrum intravenous antibiotics. We report a case of a 70 year old woman who presented with a painful erythematous rash, was admitted as a case of cellulitis, later developed worsening of symptoms and septic shock, and was diagnosed as necrotizing fasciitis.